Entrega de unidades didácticas. (UNED, 2024)
Aparece de izquierda a derecha en primer lugar Rene Muiños Gual, Eugenio Rodríguez Vega, Inés Trejos Araya, Rodrigo Arias Camacho- Rector, Alberto Cañas Escalante, y otra persona